GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 1443 species occurrences available in GBIF matching the query: TaxonKey: Epigaea repens L.. The dataset includes 1443 records from 56 constituent datasets: 138 records from NatureServe Network Species Occurrence Data. 60 records from iNaturalist research-grade observations. 3 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 1 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 42 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 1 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 5 records from California State University, Chico. 42 records from Canadian Museum of Nature Herbarium. 21 records from Field Museum of Natural History (Botany) Seed Plant Collection. 69 records from Green Plant Herbarium (TRT). 73 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from United States National Plant Germplasm System Collection. 23 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 2 records from Herbarium of The New York Botanical Garden. 115 records from CONN. 44 records from OAC-BIO Herbarium. 38 records from Botany Division, Yale Peabody Museum. 1 records from Harriet Irving Botanical Gardens (HIBG). 75 records from Michigan State University Herbarium Vascular Plants. 2 records from IAC - Herbário do Instituto Agronômico de Campinas. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from OHN. 2 records from R. L. McGregor Herbarium Vascular Plants Collection. 10 records from Missouri Botanical Garden. 5 records from MBM - Herbário do Museu Botânico Municipal. 6 records from MISS_DC_01MAR2006. 2 records from Database Schema for UC Davis [Herbarium Labels]. 1 records from Botany (UPS). 4 records from Phanerogamic Botanical Collections (S). 1 records from SysTax - Botanical Gardens. 1 records from University of Lethbridge Herbarium (LEA). 10 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 2 records from Royal Botanic Garden Edinburgh Herbarium (E). 348 records from Harvard University Herbaria. 18 records from Herbarium (UNA). 1 records from Herbario de la Universidad de Sevilla, SEV. 1 records from SANT herbarium vascular plants collection. 7 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from University of Copenhagen Arboretum. 83 records from Marie-Victorin Herbarium (MT). 10 records from H.A. Stephens Herbarium. 25 records from E. C. Smith Herbarium (ACAD). 10 records from Louisiana State University Herbarium. 1 records from USU-UTC Specimen Database. 1 records from Herbario Universidad de Antioquia (HUA). 1 records from Jardin botanique de Montréal (JBM). 1 records from UA Herbarium. 2 records from EKY_Darwincore. 29 records from Australia's Virtual Herbarium. 34 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 55 records from NMNH occurrence DwC-A. 3 records from Herbarium Berolinense. 3 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 1 records from Nationaal Herbarium Nederland.
Keywords: GBIF; biodiversity; species occurrences